Application Of Inheritance Practices From A Maqashid Sharia Perspective: A Case Study Of Banyuputih Kidul Village - Norholis (IHSA Institute, 2022)
The transition process of modernity from the time has changed it all. Includes the division of legacy treasures by the islamic society in Indonesia. In drawn on the division of heirs of arch according to islam in the past refers to the Qur’an and Hadis. While the division of heirs of the heirs in the era now on longer refers to the islamic rules it self, but the rules by his own males and customary law in the community. Then, how the maqashid sharia perspective in response to the practice of the era of now. This research uses a descriptive qualitative method of empirical with case study approach in the framework of field data analysis. The results of the study can be concluded that the application of practical distribution of the legacy of the inheritance in Banyuputih Kidul Village is dividing the heirs of the heirs of the heirs before the heir died, divide the heirs of the heirs of the heir of the heir of the water in the future, and divide the same heal estate rat men and women from the results of essert deliberations follow the desired gracies. So according ti maqashid sharia in the division of grants and the wills is in accordance with the applicable rules. While the sama distribution does not mutch the faraidl rules, due to the rights of heirs taken by other heirs. Referring to the problem the hope of the division of heirs can be implemented according to the practce of islam that gives birth to the benefit of all heirs.